Characterization of cellulosic fibers from Morus alba L. stem. Issue 4 (19th May 2019) - Prithivirajan, R.; Balasundar, P.; Shyamkumar, R.; Al-Harbi, Naiyf Sulthan; Kadaikunnan, Shine; Ramkumar, T.; Narayanasamy, P.
ABSTRACT: The chemical microstructural, physical, and thermal properties of the Morus alba L. stem fibers (MAFs) are described for the first time in this work. By analyzing the results of chemical composition, it was observed that the cellulose content of the stem of MAFs is an acceptable value when compared with other fibers and showed better results. Due to their lightweight (1316 kg/m 3 ) and the presence of high cellulose content (58.65%) with very little amount of wax (0.56%), they provide good bonding properties. In addition, analyzing the results of X-ray diffraction and Fourier transform infrared spectroscopy, we observe a degree of crystallinity of 62.06%, which is closely associated with the presence of crystalline cellulose, while the other components are amorphous. The diameter of the extracted cellulosic fibers was in the range 6–20 µm. Moreover, it was possible to identify the degradation step of each primary component of lignocellulosic fiber and to observe that it is thermally stable up to 216°C. The characterization results show that the MAF is a better replacement material for synthetic fibers because of its significant physical, chemical, and thermal properties.